Organocatalytic asymmetric synthesis of benzazepinoindole derivatives with trifluoromethylated quaternary stereocenters by chiral phosphoric acid catalysts. Issue 8 (6th February 2018) - Rahman, Abdul; Xie, En; Lin, Xufeng
Abstract : An enantioselective aza-Friedel–Crafts reaction of trifluoromethyl dihydrobenzoazepinoindoles with pyrroles or indoles catalyzed by a chiral spirocyclic phosphoric acid was developed. Abstract : An enantioselective aza-Friedel–Crafts reaction of trifluoromethyl dihydrobenzoazepinoindoles with pyrroles catalyzed by a chiral spirocyclic phosphoric acid was developed. This methodology provides a facile route to CF3 - and pyrrole-containing benzazepinoindoles bearing quaternary stereocenters in good yields and with moderate to excellent enantioselectivities (up to 93% ee). Indoles were also investigated as electron-rich aromatic substrates to afford the corresponding chiral heterocycles with good yields and considerable enantioselectivities. The introduction of CF3 shows a remarkable fluorine effect and increases the activation and stereoinduction.